Ten-year survival of ceramic-on-ceramic total hip arthroplasty in patients younger than 60 years: a systematic review and meta-analysis - Ihab Ibraheam El-Desouky; Albaraa Hassan Helal; Ali Mohamed Reda Mansour (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background Total hip arthroplasty (THA) with ceramic-on-ceramic (CoC) was created to minimise wear debris and aseptic loosening. A decade ago, a meta-analysis showed a 10-year survival rate of just 89%. Based on the excellent tribology of the current CoC, significant improvement of implant survivorship is expected. In patients younger than 60, we conducted a meta-analysis to assess 10-year survival and complications after using current primary CoC THA. Materials and methods PubMed, Scopus, EMBASE, Virtual Health Library, and Cochrane Library were used to scan for published trials that met the inclusion criteria until January 2019. The qualified studies were subjected to a systematic review and proportional analysis, and the randomised controlled trials (RCTs) were included in a comparison meta-analysis. Results Thirteen studies were included 156 findings. The total number of hips was 2278. Nine studies were cohort, and four were RCTs between ceramic and polyethylene cups. The analysis revealed an average age of 44 years (range 24–54). The 10-year survival 96% (95% CI; 95.4–96.8%), aseptic loosening rate 0.516. (95% CI; 0.265–0.903), ceramic fracture rate 0.620 (95% CI; 0.34–1.034) and squeaking rate 2.687 (95% CI; 1.279–4.593). A comparison meta-analysis revealed the risk ratio (RR) for revision was 0.27 (95% CI; 0.15–0.47), and for aseptic loosening 0.15 (0.03–0.70) favouring CoC, while RR for component fracture was 1.62 (95% CI; 0.27–9.66) favouring the polyethylene. Conclusion In patients under sixty, current CoC THAs are correlated with better 10-year outcomes than before and have high survivorship rates. Level of evidence: Level I.